INDONESIA: FROM PLURALISM TO MULTICULTURALISM - Wasino, Wasino (Paramita: Historical Studies Journal, 2013)
Indonesia was not a new entity when started to become national country. It was called a continuation of the history of the Dutch East Indies. The people lived under western colonial was a pluralistic society, people separated by social class, ethnicity, religion, race and inter-group. Between the authorities and the people separated along racial lines. In addition there was the separation of ethnic groups associated with the economic, educational and social relations. After Indonesian independence the pluralistic society situation continues. The end of the New Order has opened a Pandoras Box of poor relations between ethnic and inter-religious. As a result many conflicts occurred based on religious and ethnic differences. The conflict heated up as the influx of political interests. The process of political reform gave birth to a new awareness of the relationship between ethnicity and religion. The starting point of this change was when the President Abdurrahman Wahid unlocked barriers on multicultural relationship that respects the differences of cultural orientation among the existing ethnic. From that moment the concept of multiculturalism experienced socialization process within Indonesian society. Key words: pluralism, multiculturalism, colonial, new order, socializationÃÂ Ketika Indonesia lahir sebagai negara nasional, Indonesia bukanlahÃÂ  entitas yang baru. Ia merupakan kelanjutanÃÂ  sejarah dari masyarakat yang disebut Hindia Belanda. Masyarakat di bawah penjajah Barat ini merupakan masyarakat majemuk, masyarakat yang terpisah-pisah berdasarkan kelas sosial, suku, agama, ras, dan antar golongan. Antara penguasa dan rakyat terpisah secara garis rasial. Selain itu ada pe-misahan suku bangsa terkait dengan ekonomi, pendidikan, dan hubungan-hubungan sosial. Setelah Indonesia merdeka situasi masyarakat majemuk terus berlangsung. Berakhirnya Orde Baru telah membuka kotak pandoraÃÂ  buruknya hubungan antar etnik dan antar agama. Akibatnya banyak terjadi konflik-konflik yang berdasarkan perbedaan etnik dan agama. Hal itu semakin meruncing ketika kepentingan-kepentingan politik masuk. Proses reformasiÃÂ  politik melahirkan kesadaran baru tentang hubungan antar etnik dan agama. Titik awal perubahan ini ketikaÃÂ  Presiden Abdurahman Wahid membuka sekat-sekat hubungan multikultural yang menghormatiÃÂ  perbedaan dalam orientasi budaya di kalangan etnik yang ada. Sejak itu konsep multikulturalisme mengalami proses sosialisi dalam masyarakat Indonesia. Kata Kunci: Pluralisme, Multikultural, Kolonial, Orde Baru, Sosialisasi. ÃÂ  ÃÂ